The Role of Local Politics and Social Bio-Power in Public Information Disclosure in Wonogiri Regency - Slamet Sumarto; Wahyu Beny Mukti Setiyawan; Yulius Willy Ciptadi Angkoso; Muhammad Wildan Khunaefi (Pusat Publikasi Nusantara, 2024)
This study aims to provide an in-depth understanding of the role of local politics and socio-cultural forces in public information disclosure and offer both theoretical and practical contributions to corruption prevention efforts in Indonesia. This study employs Michel Foucault's concept of biopower as a framework to analyze and assess the political and sociocultural forces at play in Sendang village's relationship with public information transparency. The results show that the village government can serve as an important model in the implementation of transparency and accountability, as well as increasing community participation in the decision-making process. In addition, the results of this analysis show that, when properly implemented, public disclosure can be an important mechanism to facilitate more responsive and participatory governance. The contribution of this study lies in providing new insights into how local governments can be integrated into village government structures and how communities can be empowered through access to information.